Resource Description Framework (RDF) for Organised Searching on Internet - Tripathi, Aditya (DESIDOC Journal of Library & Information Technology, 2003)
This article focuses on the search performance of the existing search engines on internet. Discusses few solutions for the current searching problems, and suggests the resource description framework (RDF) for organised searching. The paper includes the usefulness of RDF schema and covers the futuristic vision of RDF. http://dx.doi.org/10.14429/dbit.21.4.3545